A new species of Rhadinella (Serpentes: Colubridae) from the Sierra Madre del Sur of Guerrero, Mexico - Campillo, Gustavo; Dávila-Galavíz, Luis Fernando; Flores-Villela, Oscar; Campbell, Jonathan A. (Zootaxa, 2016)
We describe a new species of Rhadinella from the Sierra Madre del Sur of Guerrero, Mexico, a region where the genus was previously unknown. This diminutive species is a member of a group of snakes previously allocated in the Rhadinaea godmani group, and more recently transferred to the genus Rhadinella. These snakes may have conspicuous dark longitudinal striping on a pale brown to orange background or may have dark brown to blackish dorsal ground coloration, which mostly or completely obfuscates a pattern of longitudinal striping. The new species is mostly dark with barely discernible slightly paler or darker striping (depending on how striping is interpreted). The closest relative of the new species, on the basis of morphological similarities and biogeography, appears to be Rhadinella donaji which occurs to the east in the Sierra Madre del Sur of Oaxaca about 275 km from the type-locality of the new species.